Development of an efficient particle bombardment transformation system for the endemic orchid, Phalaenopsis bellina - Chew, Yee-Chern; Wan Muhamad Asrul Nizam Wan Abdullah,; Kok, Andrew De-Xian; Janna Ong-Abdullah,; Maziah Mahmood,; Lai, Kok-Song (Penerbit Universiti Kebangsaan Malaysia, 2019)
Phalaenopsis bellina is an important indigenous orchid with high commercial value. In this study, we established an efficient particle bombardment transformation system for P. bellina using the protocorm-like-bodies (PLBs) as target tissues. Leaf derived PLBs were proliferated on ½ strength Murashige and Skoog (MS) medium supplemented with 0.8 μM 2,4 dichlorophenoxyacetic acid (2, 4-D). Both physical and biological parameters affecting the transformation system were optimised using the green-fluorescent protein (GFP) and β-glucuronidase (GUS) as reporter systems. Optimal bombardment conditions with 6 cm target tissues distance, 1100 psi acceleration pressure, 1.0 μm gold particle size, 27 mmHg chamber vacuum pressure, single bombardment time, spermidine as DNA precipitation agent, 72 h post bombardment incubation time, 2 μg plasmid DNA in 0.15:0.12 pmol ratio (pSMCHS:p35SGFP) were successfully determined. Surviving PLBs transformants were successfully recovered from the hygromycin selection medium and verified using genomic PCR analysis. The established system is not only useful for a simple and reliable transient gene analysis but as well as generating stable transformants for selective traits improvement in orchids.